The determinants of electronic publishing in Malaysia / Zahril Shahida Ahmad, Mad Khir Johari Abdullah Sani and Siti Arpah Noordin. - Ahamd, Zahril Shahida; Abdullah Sani, Mad Khir Johari; Noordin, Siti Arpah (Universiti Teknologi MARA Cawangan Selangor, 2017)
In the modern era of ICT revolution, the application of electronics medium and devices to every aspect of human life has become significant. Electronic publishing has emerged as a major development in the electronic media landscape and the adoption of this new media has become an important area of research. The continuance of electronic publishing depends on the adoption of this media by publishers and users. However, a research demonstrates that the rate of adoption of electronic publishing amongst Malaysian publishers is low. The main objectives of this study are: 1) to determine factors that facilitate the adoption of electronic publishing amongst Malaysian publishers from the perspectives of technological, organisational, environmental contexts; 2) to examine the effect of intention on electronic publishing adoption amongst Malaysian publishers; and 3) to examine the mediation effect of intention on the relationship between technological, organisational and environmental factors and electronic publishing adoption amongst Malaysian publishers. A research model is developed to identify and evaluate the key determinant factors influencing the adoption of electronic publishing amongst Malaysian publishers. This study draws on the organisation adoption theory, that is, the technology, organisation, and environment framework (TOE) to understand and explain the determinant factors of electronic publishing adoption. In addition, behavioural intention is adapted to explain the mediating effect between the independent variables (technology, organisation, and environmental factors) and the adoption of electronic publishing. Applying the quantitative method, the data collection employed a self-administered survey technique using questionnaire as the instrument.